Small Cell Ovarian Carcinomas – Characterisation of Two Rare Tumor Entities - Münstedt, K.; Estel, R.; Dreyer, T.; Kurata, A.; Benz, A. (Geburtshilfe und Frauenheilkunde, 2013)
Objective: Small cell ovarian carcinomas (SCOC) are differentiated into two types: hypercalcaemic (SCOCHT) and pulmonary (SCOCPT). Unfortunately, little is known about pulmonary-type small cell ovarian carcinoma. Study Design: We carried out a systematic analysis of all available reports in the literature on individual cases of SCOCHT and SCOCPT. Results: We found that patients with SCOCPT were significantly older than those with SCOCHT. Vimentin and chromogranin detection by immunohistochemistry allow good differentiation between the two types. Interestingly, SCOCPT but not SCOCHT was found to be associated with other benign and malignant ovarian tumours in about 44 % of cases. Although the percentage of R0/R1 resections was high (~ 74 %), survival was poor; even in patients with disease limited to the ovaries (stage Ia and Ib) the recurrence rate was 40 %. Chemotherapy with etoposide or anthracyclines could be useful. Conclusion: Taking the limitations of our study such as its retrospective nature into account and based on the results from studies of small cell carcinomas originating from other tumour sites, we conclude that treatment of SCOCPT should be based on the therapies used to treat other small cell carcinomas. Surgery is appropriate, especially in very early stages of disease, but chemotherapy should not be omitted. Newer concepts such as treatment with somatostatin analogues could help to control symptoms and stabilise some slow-growing tumours.
Keywords: ovarian cancer; ovarian tumor; ovary